2018
DOI: 10.1016/j.bbmt.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Mortality among Day +100 Survivors after Allogeneic Hematopoietic Cell Transplantation

Abstract: Although day +100 survival among allogeneic hematopoietic cell transplantation (HCT) recipients has improved over time, longer-term survival remains a challenge. The aim of this study was to identify prognostic factors for survival among patients surviving longer than 100 days using baseline characteristics and factors identified within the first 100 days after transplantation. Of 413 patients undergoing a first allogeneic HCT between 2006 and 2014, 335 survived >100 days post-transplantation. The majority und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Metronidazole days, median (IQR) ---1.5 (1,2) Abbreviations: IQR, interquartile range. a Gram-negative antibiotics included cefepime, piperacillin/tazobactam, meropenem, ceftazidime, aztreonam, and levofloxacin.…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronidazole days, median (IQR) ---1.5 (1,2) Abbreviations: IQR, interquartile range. a Gram-negative antibiotics included cefepime, piperacillin/tazobactam, meropenem, ceftazidime, aztreonam, and levofloxacin.…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%
“…Infection remains a major cause of morbidity and mortality following alloHCT [1]. Among the most common infectious complications is Clostridium difficile infection (CDI), which occurs in up to 33% of alloHCT recipients and has been identified as an independent risk factor for increased mortality [2,3].…”
mentioning
confidence: 99%
“…A recent study at the Cleveland Clinic, which examined identifying prognostic factors for survival within the first 100 days after transplantation, reported a 44% first readmission rate and 2-year NRM of 16%. Patel et al [26] found acute GVHD or more hospitalization days within the first 100 days prognostic for increased NRM. We confirmed some of these prognostic factors, although in their retrospective study, the majority of the 413 patients underwent myeloablative allogeneic HCT with marrow as graft source.…”
Section: Discussionmentioning
confidence: 99%
“…Our institutional conditioning and GVHD prophylaxis regimens have been described previously. [18][19][20][21]…”
Section: Patients and Me Thodsmentioning
confidence: 99%